ANANILSA PENERAPAN EKONOMI SYARIAH PADA UNIT USAHA BUMDes DALAM MENINGKATKAN EKONOMI MASYARAKAT DESA - Yenty Astari Dewi; Iiz Izmuddin (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
The purpose of this Writing is to analyze the study of the Implementation of Sharia Values in the business of the Nagari-Owned Business Entity (BUMNag). The analytical method used in this study is the SWOT analysis. This study shows that the contracts that exist in Islamic economics can be applied to Business Units that may be formed by BUMNag in accordance with laws and regulations. In addition to having strength (the majority of the Muslim population and Nagari have Alim Ulama, have BUMNag and good development), and Opportunities (The development of Islamic economics and the National Sharia Council, the existence of the Law concerning Islamic economics), this concept also has shortcomings (lack of public understanding of sharia contracts, lack of academic staff in Nagari) and Threats (Overall Islamic economics cannot be applied in Indonesia and the development of conventional transactions in the community). To realize BUMNag based on an Islamic economic perspective, it requires an active role and joint commitment from the Nagari government, the community, religious scholars, the National Sharia Council, non-governmental organizations, and parties concerned about the development of BUMNag and the Islamic economy.